2021
DOI: 10.1016/j.micpath.2021.104954
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals present in Indian ginseng possess potential to inhibit SARS-CoV-2 virulence: A molecular docking and MD simulation study

Abstract: Coronaviruses are deadly and contagious pathogens that affects people in different ways. Researchers have increased their efforts in the development of antiviral agents against coronavirus targeting M pro protein (main protease) as an effective drug target. The present study explores the inhibitory potential of characteristic and non-characteristic Withania somnifera (Indian ginseng) phytochemicals (n ≈ 100) against SARS-Cov-2 M pro protein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Compounds present in Azadirachta indica (n=93) and Aloe vera (L.) (n=37) were searched from different sources such as Science Direct, PubMed Central Google Scholar, Web of Science, PubMed, Scopus, Semantic Scholar, Medline, and Google Scholar (Kushwaha et al, 2021b). Marvin Sketch software (https://chemaxon.com/products/marvin) was used to prepare the structures of phytochemicals.…”
Section: Azadirachta Indica and Aloe Vera (L) Phytochemical Retrieval And Preparationmentioning
confidence: 99%
“…Compounds present in Azadirachta indica (n=93) and Aloe vera (L.) (n=37) were searched from different sources such as Science Direct, PubMed Central Google Scholar, Web of Science, PubMed, Scopus, Semantic Scholar, Medline, and Google Scholar (Kushwaha et al, 2021b). Marvin Sketch software (https://chemaxon.com/products/marvin) was used to prepare the structures of phytochemicals.…”
Section: Azadirachta Indica and Aloe Vera (L) Phytochemical Retrieval And Preparationmentioning
confidence: 99%
“…Literature showed that, MM-PBSA method could effectively estimate the fee energy of binding of the docked complexes. Although it requires high computational cost, it can still provide near accurate result than the conventional molecular docking technique [ 43 , 44 ]. The results showed that when compared with the control drug Chloroquine (ΔG binding −90.89 ± 12.33 KJ mol −1 ), Curcumin had a very high binding affinity (ΔG -180.04 ± 15.16 KJ mol −1 ) towards the receptor protein Omicron S. Further, this observation was supported by higher contribution of other energy terms namely ΔG Non polar, ΔG Electrostatic and ΔG Van der Waal as shown in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The computer-assisted molecular docking simulation tool is very useful in computational biology study to determine the accuracy and stability of the docked complex in a near-native physiological environment. Kushwaha et al [ 111 ] recently exhibited the binding stability of quercetin-3-rutinoside-7-glucoside at the active site of SARS-Cov-2 M pro by using MD simulation tool. Similarly, Islam et al [ 112 ] use MD simulation tool to evaluate the docking potential of the selected phytochemicals against the main protease of SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%